ENRICHING STUDENTS’ VOCABULARY THROUGH DIRECTED READING ACTIVITY (DRA) - Maryam Nurdin Ibrahim (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2017)
In this research, the researcher wants to see the enrichment of the students ‘ vocabulary through Directed Reading Activity (DRA). The aim of this research is to analyze the students’ difficulty in having vocabulary and to analyze the process of Directed Reading Activity in class. The subject of this research is the students in class X of Tourism Department in SMKN 1 Gorontalo. This research is conducted from April to June 2010. This action research used Kemis and Taggart design which involved four components : planning, acting, observing and reflecting. The data was collected by using observation sheet, questionnaire and test. Questionnaire and test based on the indicators of this research. The conclusion of this research is the students’ vocabulary increased when DRA is applied.